Problem N 10
we have the function
![f(x)=9+√(4x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/v9eib2se3fts0ahpd5upv0gow9k1i95lcq.png)
Find out the inverse
Let
y=f(x)
![y=9+4x-4](https://img.qammunity.org/2023/formulas/mathematics/college/bycjhk7lc4gggb1kche687vm8ybeqerdo1.png)
step 1
Exchange the variables (x for y and y for x)
![x=9+√(4y-4)](https://img.qammunity.org/2023/formulas/mathematics/college/o5cty89ril8uq0zc0o3ns0ik5oxw5zyz27.png)
step 2
Isolate the variable y
![\begin{gathered} x=9+√(4y-4) \\ x-9=√(4y-4) \\ squared\text{ both sides} \\ (x-9)^2=4y-4 \\ 4y=(x-9)^2+4 \\ y=((x-9)^2)/(4)+(4)/(4) \\ \\ y=((x-9)^(2))/(4)+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ugku149mqrq25z8ld9rhlbh288cuwhqdiy.png)
therefore
The inverse function is
![f^(-1)(x)=((x-9)^(2))/(4)+1](https://img.qammunity.org/2023/formulas/mathematics/college/j5x8i7h044efovb60lcf99gz5oidshvstj.png)
Problem N 11
we have the function
![f(x)=√(6x-8)+5](https://img.qammunity.org/2023/formulas/mathematics/college/y2hif3s6p1qq9q6uf3an8i8o4xtkgkolxc.png)
Find out the inverse
Let
y=f(x)
![y=√(6x-8)+5](https://img.qammunity.org/2023/formulas/mathematics/college/dp1fnd8d4ifaqf85mgfm3g6r4vuywpdrjh.png)
Exchange the variables
![\begin{gathered} x=√(6y-8)+5 \\ isolate\text{ the variable y} \\ x-5=√(6y-8) \\ squared\text{ on both sides} \\ (x-5)^2=6y-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a0fdbj3u7cmjweigmp84irjtkpj0koh0q1.png)
isolate the variable y
![\begin{gathered} 6y=(x-5)^2+8 \\ y=((x-5)^2)/(6)+(8)/(6) \\ \\ y=((x-5)^(2))/(6)+(4)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s8qtnhtewafg97urx695p30m4lmdv6dp9e.png)
therefore
The inverse function is equal to
![f^(-1)(x)=((x-5)^(2))/(6)+(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/euhgq3zqipaumdhmohsgimg2dxizsx7wjm.png)